IMPROVING STUDENTS’ LANGUAGE PROFICIENCY THROUGH READING - Barno Shamsematova (Web of Journals Publishing, 2024)
The importance of reading for students in developing their language proficiency has received a lot of attention in the field of language education. Using a variety of empirical studies and theoretical frameworks, this article offers a thorough review and analysis of the effectiveness of using reading as a tool to improve students' language proficiency.